ANALISIS FATWA DSN-MUI NOMOR: 4/DSN-MUI/IV/2000 TENTANG AKAD MURABAHAH DALAM PENERAPAN HAK MILIK - Andi Asruni; Zainal Said; Damirah (BANCO: Jurnal Manajemen dan Perbankan Syariah, 2022)
Bank Muamalat KCP Parepare is one of the Islamic banks whose operational activities implement a murabahah financing system. Regarding murabahah itself, it is clearly regulated in the DSN MUI fatwa No: 04/DSN-MUI/2000, concerning murabahah which states that "banks buy goods needed by customers on behalf of the bank itself and this purchase must be legal and free from usury". Meanwhile, in practice, the bank as the seller gives freedom to the customer to find the desired goods or vehicle for himself. This research is a field research using a qualitative approach. Data collection techniques used are observation, interviews, and documentation. The data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study note that the application of property rights in the murabahah contract at Bank Muamalat KCP Parepare where the murabahah object legally belongs to the muamalat bank then a murabahah contract is held with the customer. So that there is a transfer of ownership of the murabahah object that previously belonged to the bank and then became the property of the customer. This is of course in accordance with the fatwa No.04/DSN-MUI/IV/2000 concerning murabahah. The application of ownership rights at Bank Muamalat KCP Parepare can be said to be Al-Milk at-tam (perfect ownership) because after the implementation of the contract and signing of the contract, the murabahah financing object has become the legal property of the customer, meaning there is a transfer of ownership so that all rights and uses related to the object of the contract is fully the power of the customer.